2013
DOI: 10.1080/01419870.2013.826811
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future: revisiting the contact hypothesis at Turkish and mixed non-profit organizations in Amsterdam

Abstract: This paper revisits the contact hypothesis by assessing differences in generalized trust among participants of Turkish non-profit organizations and ethnically mixed organizations in Amsterdam. Most voluntary sector research takes the contact hypothesis at its core and assumes that the concentration of ethnic minorities in non-profit organizations is detrimental to learning generalized trust. These studies assume that diversity within organizations is better for developing generalized norms without examining pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A less-optimistic corollary to this literature predicts that being involved in less-diverse organizations has a negative effect on generalized trust as homogeneity inhibits the learning of cooperation beyond the in-group (cf. Achbari, 2015; Marschall & Stolle, 2004; Newton, 1999; Paxton, 2007; Putnam, 2000; Stolle & Rochon, 1998; Theiss-Morse & Hibbing, 2005; Uslaner, 2002; Uslaner & Conley, 2003). The theoretical underpinning of these expectations is that interaction among people of a similar ethnic background creates an in-group bias, where trust is developed only toward an in-group and hostility is developed toward out-groups (for discussion, see Stolle, Soroka, & Johnston, 2008).…”
Section: Theory: the Civic Engagement And Generalized Trust Nexusmentioning
confidence: 99%
See 1 more Smart Citation
“…A less-optimistic corollary to this literature predicts that being involved in less-diverse organizations has a negative effect on generalized trust as homogeneity inhibits the learning of cooperation beyond the in-group (cf. Achbari, 2015; Marschall & Stolle, 2004; Newton, 1999; Paxton, 2007; Putnam, 2000; Stolle & Rochon, 1998; Theiss-Morse & Hibbing, 2005; Uslaner, 2002; Uslaner & Conley, 2003). The theoretical underpinning of these expectations is that interaction among people of a similar ethnic background creates an in-group bias, where trust is developed only toward an in-group and hostility is developed toward out-groups (for discussion, see Stolle, Soroka, & Johnston, 2008).…”
Section: Theory: the Civic Engagement And Generalized Trust Nexusmentioning
confidence: 99%
“…To be sure, the bulk of the evidence about the detrimental effects of ethnic diversity on generalized trust comes from analyses examining the proximity of ethnic groups in neighborhoods and countries (see Van der Meer & Tolsma, 2014). There is little empirical work investigating a potentially positive socialization effect arising from proximity of multiple ethnic groups in bridging—as opposed to bonding—voluntary organizations (for example see, Achbari, 2015, 2016; Rapp & Freitag, 2015; Stolle, 1998). Because voluntary organizations often consist of smaller units than society-at-large, the proximity of out-groups in those settings may more readily translate into intergroup contact.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-setting, that is, the level of everyday life encounters such as in restaurants, cafes, or public transport stations, is rarely studied. A rich social sciences tradition shows that contextual diversity in spaces, such as associations (Van der Meer 2016), schools (Janmaat 2015), leisure (Schaeffer 2013), consumption (Radice 2016), the workplace (Kokkonen, Esaiasson, and Gilljam 2015), or social organizations (Achbari 2015), provides important meeting opportunities for people of different backgrounds. Based on the contact theory framework, research has argued that regular exposure enhances knowledge about the outgroup, reduces anxiety about intergroup contact, increases empathy, and facilitates general trust (e.g., Hewstone 2003; Stephan and Stephan 2000; Pettigrew and Tropp 2008).…”
mentioning
confidence: 99%
“…In doing so, prejudice toward each others’ groups as a whole is reduced. Numerous studies have shown the effectiveness of contact (Achbari, 2015; Alperin, Hornsey, Hayward, Diedrichs, & Barlow, 2014; Broad, Gonzalez, & Ball-Rokeach, 2014; Ellison, Shin, & Leal, 2011; Mähönen, Ihalainen, & Jasinskaja-Lahti, 2013; McKeown & Dixon, 2017; Shook & Fazio, 2008; Span, 2011).…”
mentioning
confidence: 99%